2017
DOI: 10.1016/j.bbadis.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Total abdominal irradiation exposure impairs cognitive function involving miR-34a-5p/BDNF axis

Abstract: Radiotherapy is often employed to treat abdominal and pelvic malignancies, but is frequently accompanied by diverse acute and chronic local injuries. It was previously unknown whether abdominal and pelvic radiotherapy impairs distant cognitive dysfunction. In the present study, we demonstrated that total abdominal irradiation (TAI) exposure caused cognitive deficits in mouse models. Mechanically, microarray assay analysis revealed that TAI elevated the expression level of miR-34a-5p in small intestine tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…The results, summarized in Table 2, highlight the role of gut microbiota in regulating neuroinflammation, cerebral amyloid deposition and clearance, hippocampal synthesis of mediators or receptors involved in neurotransmission 5054. Bacterial metabolites and circulating miRNAs have been hypothesized as playing a pivotal role in this gut–brain crosstalk 52,53. Interestingly, antibiotic-induced dysbiosis may not necessarily imply unfavorable consequences on brain pathology.…”
Section: Resultsmentioning
confidence: 99%
“…The results, summarized in Table 2, highlight the role of gut microbiota in regulating neuroinflammation, cerebral amyloid deposition and clearance, hippocampal synthesis of mediators or receptors involved in neurotransmission 5054. Bacterial metabolites and circulating miRNAs have been hypothesized as playing a pivotal role in this gut–brain crosstalk 52,53. Interestingly, antibiotic-induced dysbiosis may not necessarily imply unfavorable consequences on brain pathology.…”
Section: Resultsmentioning
confidence: 99%
“…A management of the microbiota and its effects on miRNAs could also have important results in preventing damage from radiotherapy. One group of researchers has demonstrated that radiation can influence the structure of gut microbiota and miRNAs expression [82,83], while faecal microbiota transplantation from healthy subjects may present a therapeutic option for radiation-provoked toxicity [84]. Moreover, high-throughput sequencing of microbial 16S rRNA and host miRNA demonstrated that simvastatin or high-fat diet block radiation-altered enteric bacterial taxonomic structure and protect miRNA expression profile [85].…”
Section: Discussionmentioning
confidence: 99%
“…It can up-regulate miR-34a-5p expression and change bacterial composition, mediating cognitive dysfunction by targeting Bdnf, which has been reported to participate in many neurodegenerative disorders (Zuccato and Cattaneo 2009 ). Interestingly, the inhibition of miR-34a-5p by an antagomir could alleviate TAI-mediated cognitive impairment and restore the composition of the gut microbiota (Cui et al 2017 ). Therefore, it is reasonable to speculate that the gut microbiota is associated with cognitive impairment, which can be regulated by miR-34a-5p.…”
Section: The Gut Microbiota–mirna Interactions In Central Nervous Sysmentioning
confidence: 99%